How safely can we follow up post-term pregnancy with uncertain gestation using amniotic fluid index measurement - Mohamed, Amenah Mahmoud Mustafa (Stellenbosch : Stellenbosch University, 2013)
Thesis (MMed)-- Stellenbosch University, 2013.